Sonographic indicators of isolated fetal sagittal craniosynostosis during pregnancy. Issue 5 (12th June 2020) - Constantine, Sarah; Kiermeier, Andreas; Anderson, Peter
Abstract: Introduction: The antenatal diagnosis of sagittal craniosynostosis can be challenging, but there are several published papers describing a traumatic outcome to both the affected fetus and the mother during delivery of a scaphocephalic child. The antenatal imaging from affected children was collected along with the mother's obstetric history. The aim of this study was to identify antenatal ultrasound features that may assist the diagnosis of sagittal synostosis before birth, to enable appropriate delivery planning and avoid both maternal and fetal trauma during birth. Methods: Antenatal ultrasound scans in both the second and third trimesters were traced for 36 children with sagittal synostosis. The initially diagnostic CT scans were also sourced. A delivery history was collected from the hospital case notes where available. Results: The affected group showed a statistically significant reduction in cephalic index during the second half of pregnancy compared with the normal population which became slightly more brachycephalic ( P = 0.001). Regression analysis showed an average reduction in cephalic index of 0.57 units per month. There was also a much higher rate of malpresentation and surgical deliveries in the affected group than the normal population. There was a relationship between sagittal craniosynostosis and breech presentation and an associated higher rate of surgical deliveries. Conclusion: It is possible to detect sagittal synostosis in the third trimester of pregnancy which may assist with delivery planning.